Characteristics of Domperidone Patch With Variation of Penetration Enhancers (Isopropyl Myristate And Eucalyptus Oil) - elfiyani, rahmah (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Domperidone undergoes first-pass metabolism in the liver, indicating a low bioavailability value when administered orally. To overcome this, domperidone was given transdermally as a patch dosage form. The thing that must be considered in administering a drug via transdermal is the diffusion profile of the active substance. Penetration enhancer was one component that can increase the diffusion of domperidone formulated in patch preparations. The study aimed to compare the penetration-enhancing ability of isopropyl myristate (IPM) and eucalyptus oil (EO) on the diffusion profile of the domperidone patch (DP). DP was made by solvent casting method using HPMC polymer and penetration enhancer (IPM and EO) with concentrations of 2%, 5%, and 10%, respectively. DP evaluations were organoleptic, weight uniformity, thickness, moisture content, drug content, and diffusion. DP had the appearance of a round shape with a diameter of 0.9 cm, white, dry, and not cracked. The results of weight uniformity in DP-IPM ranged from 111.19-140.23 mg while DP-EO ranged from 103.01-128.2 mg, the thickness of DP-IPM ranged from 1.64-1.72 mm while DP-EO ranged from 1.65-1.72 mm, moisture content of DP-IPM ranged from 5.71-7.16% while DP-EO ranged from 5.33-6.85%, drug content of DP-IPM ranged from 100.62-101.06% while DP-EO ranged from 99.23-100.35%. The results of the diffusion profile showed that the diffusion kinetics of DP-IPM and DP-EO were zero order, and the rate of diffusion of DP-IPM ranges from 31.448-37.612 ppm/hour while DP-EO ranges from 30.102-35.394 ppm/hour. The conclusion was that penetration enhancers (IPM and EO) do not affect the diffusion kinetics of PD, but the diffusion rate of DP-IPM is higher than DP-EO.